Nowe prawo o pieczy nad pełnoletnim - Schlüter, Wilfried; Liedmeier, Norbert (Wydział Prawa i Administracji UAM, 1990)
The law on custody over adults in force in the Federal Republic of Germany is the expression of the XIXth c. ideas. Presently, legislative works on the amendment of the said law are in progress. They aim at taking into account to a greater extent a humane aspect and at making legal provisions more flexible, thus making it possible to adjust legal procedure and a court decree to an individualised situation of a handicapped person.
New law on custody over adults